2000
DOI: 10.1021/bi0007021
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of GLUT4 and GLUT1 Recycling by Insulin in Rat Adipocytes:  Kinetic Analysis Based on the Involvement of Multiple Intracellular Compartments

Abstract: The trafficking kinetics of GLUT4 and GLUT1 in rat epididymal adipocytes were analyzed by a four-compartment model based upon steady-state pool sizes of three intracellular fractions and one plasma membrane fraction separated and assessed under both basal and insulin-stimulated states. The steady-state compartment sizes provided relative values of the kinetic coefficients characterizing the rate of each process in the loop. Absolute values of these coefficients were obtained by matching the simulated half-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 28 publications
(72 reference statements)
3
30
0
Order By: Relevance
“…Whereas a very small percentage of insulin receptors are needed for maximal signaling, all Glut4 molecules are involved in trafficking and Glut4 attains a steady-state distribution, cell surface versus internal, ?10 min after insulin exposure, when exocytic and endocytic rates are equal (69)(70)(71). In this time frame, we see no evidence that any insulin-dependent changes occur in cell surface caveolae composition (34), consistent with the finding that bulk caveolae are not very dynamic structures (72,73).…”
Section: Cellular Spelunkingsupporting
confidence: 72%
“…Whereas a very small percentage of insulin receptors are needed for maximal signaling, all Glut4 molecules are involved in trafficking and Glut4 attains a steady-state distribution, cell surface versus internal, ?10 min after insulin exposure, when exocytic and endocytic rates are equal (69)(70)(71). In this time frame, we see no evidence that any insulin-dependent changes occur in cell surface caveolae composition (34), consistent with the finding that bulk caveolae are not very dynamic structures (72,73).…”
Section: Cellular Spelunkingsupporting
confidence: 72%
“…8). Despite the fact that insulin treatment triggers both GLUT4 and GLUT1 (to a lesser extent) translocation in 3T3-L1 adipocytes, it has been reported that these two glucose transporters are stored in separate intracellular compartments, utilizing different machinery for translocation (31,37,41). In fact, overexpressing the constitutively active form of Akt induces GLUT4, but not GLUT1, translocation (16).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the intracellular storage sites of these glucose transporters are different. Insulin-induced GLUT1 translocation is much weaker than that of GLUT4 and involves a different signal transduction pathway (16,31,37,41). In order to investigate whether PBP10 treatment primarily affects signals specific for GLUT4 translocation, we looked at the effect of PBP10 treatment on GLUT1 translocation.…”
Section: Pbp10 Inhibits Insulin-induced Glut1 Translocationmentioning
confidence: 99%
“…From extensive research on GLUT4 translocation in adipocytes, it would seem that a net transporter redistribution to the sarcolemma upon exposure of cardiac tissue or cells to a given stimulus is caused by an increase in the rate of exocytosis without any change in the rate of endocytosis (which is regarded as noninducible in this translocation model). This is currently the most favored view of the regulation of transporter translocation (207,365,428), although a decreased endocytosis may also contribute to net GLUT4 translocation (263). Nevertheless, in general, endocytosis is regarded as an unregulatable (housekeeping) trafficking event, while in contrast exocytosis is highly inducible.…”
Section: Signaling and Trafficking Events Regulating Membrane Tranmentioning
confidence: 99%